Analysis of the Digital-Based Information System Learning Process on Student Readiness in the Digital Era - Irwansyahputra, Muhammad; Syahputra, Muhammad Riza; Chandra, Suherman (Jurnal Mekintek : Jurnal Mekanikal, Energi, Industri, Dan Teknologi, 2025)
North Sumatra has several universities in various regions spread across 33 regencies/cities, where the number of students studying at several universities in North Sumatra according to the higher education database (PDDIKTI) is 130,182 students. As many as 25 percent of the number of students at several universities in North Sumatra who understand the use of information systems at the universities where they study, affect students' readiness to understand information system learning, which reduces students' understanding and knowledge, as well as their competence in knowing the contents of the material, understanding learning objectives, and understanding information system applications for decision making. This study aims to determine and analyze the extent to which the digital-based information system learning process influences students' readiness to understand learning using information systems in the digital era. The research method uses a quantitative descriptive method with a sampling technique using the accidental sampling method, and data collection techniques are carried out using observation, distributing questionnaires and documentation studies. The results of the study describe that the process of learning digital-based information systems has an effect on students' readiness in understanding learning information systems in the digital era, where students must be able to improve their knowledge, understanding and skills sufficiently by reading books and other literature, as well as increasing their applied knowledge about information systems in the digital era in order to be able and ready to improve their understanding of learning information systems.